PENGARUH SIKAP KONSUMEN DAN NORMA SUBYEKTIF TERHADAP NIAT BELI MOBIL TOYOTA AGYA DI KOTA DENPASAR - Novia Mandasari, Roselina Ni Putu; Nurcaya, I Nyoman (E-Jurnal Manajemen, 2013)
Purchase intention is influenced by factors both internal and external factors (the social environment). Internal factors include consumer attitudes and subjective norms (influence of others) are the external factors. Consumer attitudes shaped by the belief in the object attributes and attribute evaluation to quantify the benefits that consumers want to be perceived. Whereas subjective norms in the purchase formed by faith in the opinions of others and motivation to follow the opinions of others. The research was conducted in the city of Denpasar. Number of samples taken 100 small and medium-sized businesses with non-probability sampling methods, especially purposive sampling. The data was collected using a questionnaire. The analysis technique used is multiple linear regression. Based on the analysis it was found that attitudes toward the attributes of Toyota Agya significant effect on purchase intentions Toyota Agya. This suggests that the better attitudes toward attributes such as car design, brand image or brand, price, and color choices will increase purchase intention. Similarly, subjective norms significantly influence purchase intention Toyota Agya. This indicates the greater subjective norms (influence of others) as influences or opinions of parents, close friends and business associates in a purchase will also increase purchase intention.   Keywords : attitudes, subjective norms, purchase intention